Identification and mapping of risk areas of rhino poaching; a geospatial approach: A case study from eastern sector of Chitwan National Park, Nepal - Subedi, M.; Subedi, R. (Banko Janakari, 2018)
Nepal has an appreciative history on conservation of rhino with remarkable proportions of Asian rhino population protected and managed within the protected areas. Poaching risk map promises early warning and a way to target preventive action, which can safeguard both human and ecosystem. This study was designed to identify and map risk areas of rhino (Rhinoceros unicornis) poaching within and around eastern sector of Chitwan National Park (CNP). A multi criterion GIS method was used to analyze and derive the risky zone. A binary logistic regression and expert consultation were done to finalize variables and risk rating, then weighted sum index model was performed in ArcGIS to derive risk zonation map. Presence/poaching and pseudo absence data were dependent variables and distance to guard post, settlement and road network from poaching events, land cover, slope and elevation were predictor variables for logistic regression model. Poaching events were observed to be spatially distributed around the park except in the south part. Among the seven predictable variables, five variables except terrain (slope and elevation) were statistically significant at 10% level of test (p<0.1). The poaching risk map indicates that areas near to roads, far from the guard post, and densely populated area of grasslands are high risk zone areas for rhino poaching. The GIS based maps will be practical and strategically to wildlife managers in CNP to facilitate decision making on intervention programmes and how best to direct law enforcement patrol within and around the park. Banko Janakari A Journal of Forestry Information for Nepal Vol. 27, No. 2, 2017, Page: 12-20